Fingolimod Therapy in Early Multiple Sclerosis: An Efficacy Analysis of the TRANSFORMS and FREEDOMS Studies by Time Since First Symptom. (31st March 2014) - Agius, Mark; Meng, Xiangyi; Chin, Peter; Grinspan, Augusto; Hashmonay, Ronny
Summary Aims The phase 3 TRANSFORMS and FREEDOMS studies established the efficacy of fingolimod in reducing multiple sclerosis (MS) relapses and magnetic resonance imaging lesions compared with intramuscular (IM) interferon (IFN) β‐1a and placebo over 12 and 24 months, respectively. Methods To investigate the efficacy of fingolimod at the approved 0.5 mg dose in patients early in the MS disease course, post hoc subgroup analyses of TRANSFORMS (n = 272) and FREEDOMS (n = 217) data were conducted in patients who experienced their first MS symptom <3 years before randomization. Results Fingolimod 0.5 mg reduced annualized relapse rate by 73.4% (P = 0.0002) versus IFNβ‐1a IM and by 67.4% (P < 0.0001) versus placebo in patients with <3 years since first symptom; respective reductions were 45.4% and 51.4% in subgroups of patients with ≥3 years since first symptom. For patients with <3 years since their first symptom, significantly fewer new/newly enlarged T2 lesions were observed with fingolimod versus IFNβ‐1a IM (mean number, 1.94 vs. 2.95; P = 0.036) or placebo (4.1 vs. 10.7; P < 0.001); the mean number of gadolinium‐enhancing T1 lesions was significantly reduced versus placebo (0.3 vs. 1.1; P < 0.001). Conclusion Fingolimod 0.5 mg is highly effective in reducing relapses and MRI activity in patients early in the MS disease course.